In Whose Interest? Ante-Bellum Abolitionism, the Bible, and Contemporary Christian Ethics - Carson Marion L. S. (Perichoresis: The Theological Journal of Emanuel University, 2018)
Christians look to Scripture to inform their ethical decision-making, believing that God speaks through it. However, disagreement as to what the Bible requires us to do can often lead to acrimonious splits within the church. So long as sharp divisions amongst Christians over ethical issues remain, injustices continue, and the reputation of the church is undermined. This article suggests that lessons may be learned from the story of the use of the Bible in the American Abolitionism debate which can help the contemporary church to discuss and perhaps even resolve some enduring ethical questions which are dividing Christians today.